ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH KOTA TEGAL - Nadya Fazriana Haniz; Hadi Sasana (Universitas Diponegoro, 2014)
This research aims to analyze the factors that affect tax revenues the city of Tegal for 20 years of observation, that is, since 1991th until 2010th. Types of data used in this research is the secondary data were obtained from the Bureau of Statistics Central (BPS), the Department of Revenue and Asset Management Areas (DPPAD) of Tegal. The Data retrieved is the data of receipt tax area, per-capita income, taxpayer, inflation, and economic growth. Results of analysis showed that the per-capita income, taxpayers, and economic growth in the city of Tegal since 1991th until 2010th had a significant influence on the tax revenue in city of Tegal, while inflation did not influence significantly to tax revenues in the city of Tegal.